Industrial surplus heat transportation for use in district heating. (1st September 2016) - Chiu, J.NW.; Castro Flores, J.; Martin, V.; Lacarrière, B.
Abstract: M-TES (Mobile Thermal Energy Storage) technology is explored in this paper for transportation of industrial surplus heat for use in LTDH (low temperature district heating network). LTDH has promising potential in utilizing low grade heat, on the other hand, 20%–50% of industry generated surplus heat is often released to the ambient environment. M-TES is used to match thermal energy supply and demand that occur at different locations and that are shifted in time. In this paper, design of M-TES is conducted, optimization in operating strategies is performed, sensitivity analysis on levelized cost is studied, and environmental impact of CO2 emissions due to transportation is evaluated. The results of the study show an array of transportation means and storage operating strategies under which M-TES is technically, economically and environmentally sound for transportation of industrial surplus heat for use in LTDH network. Highlights: Phase change material is adequate for use in mobile energy storage. Industrial surplus heat utilization is successfully demonstrated. Techno-economic optimized control strategy leads to 25% reduction in cost. Transportation is the main contributing factor in cost and CO2 emissions.